GAMBARAN TIPE KEPRIBADIAN SISWA DI SMP NEGERI 01 KABUPATEN BENGKULU UTARA - zumkasri zumkasri; susi hardianti (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2018)
This study aims to find out how the personality type description of students in State Middle School 01 North Bengkulu Regency. In this study, the analysis was focused more on sanguistic, melancholy, choleric, and pleasing personality. This type of research is quantitative descriptive research, namely research based on the philosophy of positivism, used to examine certain populations or samples, collecting data using instruments, analyzing data is quantitative. The sample of this study was 10% of the total number of students in SMP Negeri 01 Bengkulu Utara so the number of samples was 60 students. Data collection techniques in this study used a questionnaire. Data analysis techniques in this study The analysis used in this research is descriptive percentage to process data and describe data using the percentage formula. The findings of this study are that the description of personality types of students varies, this is evidenced by the results of the percentage calculation with Sanguinis personality type by 77%, Melancholic personality type by 2%, Cholesterol personality type by 3%, and Plegmatic personality type by 18%.